PEMBUATAN DASHBOARD GEMPA BUMI DI INDONESIA - Rusdi, Zyad (Computatio : Journal of Computer Science and Information Systems, 2022)
Abstract Earthquakes are one of the most frequent disasters in Indonesia in recent years. Earthquakes often strike the country of Indonesia because Indonesia is located along tectonic paths so that earthquakes become an unavoidable disaster and my goal in conducting this research is to show data on earthquakes that occurred in Indonesia during the last few years from 2008 to 2018. Earthquakes also have risks. which is quite large depending on the strength of the earthquake produced, the higher the strength of the earthquake, the greater the risk that will be caused to the risk of a tsunami. The data used are date, area, earthquake strength, victims and damage caused by the earthquake for the manufacture of earthquake dashboards in Indonesia and the purpose of making dashboards to provide information to users about earthquake events that occurred in Indonesia through the dashboard display to make it easier for users to understand the data. presented through the dashboard. The dashboard creation will be done using the Power BI application. The method used is the waterfall method because it has a clear flow from beginning to end.